Pengaruh Literasi Keuangan, Orientasi Pasar, dan Orientasi Kewirausahaan Terhadap Kinerja Pemasaran UMKM Egg Roll Waluh di Kecamatan Cepu, Kabupaten Blora - Fike Meidiva (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2019)
The purpose of this study was to determine the effect of Financial Literacy, Market Orientation, and Entrepreneurship Orientation on the Marketing Performance of Egg Roll Waluh SMEs in Cepu District, Blora Regency. This research uses descriptive quantitative research methods. The sampling technique used is a saturated sample, with a sample of 100 respondents from SMEs Egg Roll. The data analysis used descriptive analysis, multiple regression analysis, and saw the coefficient of determination. The results obtained showed that 1) There was a positive and significant influence between financial literacy on the marketing performance of Egg Roll Waluh SMEs in Cepu District, Blora Regency. (2) There is a positive and significant influence between market orientation on the marketing performance of Egg Roll Waluh SMEs in Cepu District, Blora Regency. (3) There is a positive and significant influence between entrepreneurial orientation on the marketing performance of Egg Roll Waluh SMEs in Cepu District, Blora Regency. (4) There is a positive and significant influence between financial literacy, market orientation, and entrepreneurial orientation on the marketing performance of Egg Roll Waluh SMEs in Cepu District, Blora Regency.